LIMITED SEED DISPERSAL MAY SHAPE GENETIC STRUCTURE OF Hydnophytum formicarum Jack. POPULATIONS IN MANGROVE ECOSYSTEM - Abdul Shukor Yusoff; Wan Bayani Wan Omar; Shahrudin Rohani (BIOTROPIA, 2020)
Hydnophytum formicarum is an epiphytic plant commonly distributed throughout Southeast Asia. However, its distribution is currently declining due to forest fragmentation and the subsequent habitat changes, which may have also affected the genetic structure of H. formicarum populations. Hence, this study aimed to understand the genetic variation and differentiation within and among populations of this species. Using Random Amplified Polymorphic DNA (RAPD) markers, the genetic variation and genetic differentiation among three populations were assessed to identify potential conservation management strategies for this species in the mangrove ecosystem in Malaysia. Ten highly reproducible primers were used in the population analysis, resulting in a total of 221 discernible fragments. Genetic variation among populations was high at 98% polymorphic fragments. AMOVA showed significant genetic differentiation among the populations (PT = 0.554, p ≤ 0.001), with pairwise genetic distances between the populations ranging from 0.495 to 0.589. PCoA clustering analysis separated the populations according to their geographical locations. The high genetic variation within populations, high genetic differentiation between populations, and clear separation in the cluster analysis indicate restricted seed dispersal of the species.